Spot Urine Sodium-to-Potassium Ratio Is a Predictor of Stroke: The MESA. Issue 2 (February 2019) - Averill, Michelle M.; Young, Rebekah L.; Wood, Alexis C.; Kurlak, Emily O.; Kramer, Holly; Steffen, Lyn; McClelland, Robyn L.; Delaney, Joseph A.; Drewnowski, Adam
Abstract : Background and Purpose—: Dietary sodium reduction with concurrent increase in potassium intake is a current public health priority to reduce risk of cardiovascular events. This study explored associations between the spot urine sodium-to-potassium ratio and cardiovascular events in the MESA (Multi-Ethnic Study of Atherosclerosis) longitudinal cohort. Methods—: The MESA is a prospective cohort study of 6814 adults from 4 ethnic groups (European-, Asian-, African- and Hispanic-American) with a mean age of 62 (±10.2) years and an average of 11.7 (±2.2) years of follow-up. Participants were free of clinical cardiovascular disease at baseline. Spot urine sodium and potassium excretion, as a marker of dietary intake, was collected at baseline. The impact of urinary sodium-to-potassium ratio on adjudicated cardiovascular events was assessed using Cox proportional hazards models. Results—: Only 39% of MESA participants had a urinary sodium-to-potassium ratio ⩽1, and these participants experienced only 74 of the 236 strokes. A sodium-to-potassium ratio >1 was associated with a hazard ratio of 1.47 (95% CI, 1.07–2.00) for risk of stroke, adjusting for age, sex, race, cardiovascular risk factors, socio-demographic characteristics, body size, and kidney function. Conclusions—: The spot urine sodium-to-potassium ratio (measurable in routine care) is associated with stroke. A urine sodium-to-potassium ratio of ⩽1, may be related to a clinically relevant reduction in stroke risk and is a feasible target for health interventions. Abstract : Supplemental Digital Content is available in the text.